2016
DOI: 10.4028/www.scientific.net/kem.682.356
|View full text |Cite
|
Sign up to set email alerts
|

Application of Torsion Test for Determination of Rheological Properties of 5019 Aluminium Alloy

Abstract: The paper presents the results of the study aimed at determination of plasticity of hard-deformed aluminium alloy grade 5019 in terms of parameters characteristic for the process of extrusion. The examinations were carried out in hot torsion test. Using the developed mathematical model of the analyzed alloy the mathematical modelling of torsion test was also performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 6 publications
0
6
0
1
Order By: Relevance
“…In paper [7] it is shown that existing methods of testing specimens by torsion, such as [8][9][10][11][12][13], do not allow to study the rheological properties of steels and alloys sensitive to the strain rate, in the hot state for example. In order to ensure the reliability of the obtained data on the strain resistance with the use of torsion tests,…”
Section: The Torsion Testing Methods With Variable Grip's Accelerationmentioning
confidence: 99%
“…In paper [7] it is shown that existing methods of testing specimens by torsion, such as [8][9][10][11][12][13], do not allow to study the rheological properties of steels and alloys sensitive to the strain rate, in the hot state for example. In order to ensure the reliability of the obtained data on the strain resistance with the use of torsion tests,…”
Section: The Torsion Testing Methods With Variable Grip's Accelerationmentioning
confidence: 99%
“…where φ is angle of twist of the sample, equal to the angle of rotation of the grippers of the testing machine, l is length of the working cylindrical part of the sample. Known works in which a working part of the specimen is formed as a recess along the radius [16]. It is asserted that when using such samples, the drift phenomenon of the section with maximum deformation is absent and during deformation up to the moment of sample destruction the maximum deformation is localized in the cross section of the neck with the smallest diameter.…”
Section: Methods For Determining the Hardening Curves By The Torsionmentioning
confidence: 99%
“…При этом деформирование рассматривалось как квазистатическое, несмотря на зависимость деформационной кривой от скорости воздействия. Наличие эффекта зуба текучести для металлов наблюдается на скоростях деформации порядка 10 2 −10 3 s −1 [22,23], а также на скоростях деформации 10 −2 −10 1 s −1 [24][25][26]. На основе кинетического варианта модели релаксационной пластичности максвелловского типа [3,4] в работе [27] для меди, кадмия и стали были спрогнозированы динамические эффекты, в том числе эффект зуба текучести, наблюдаемые на скоростях деформации 10 −5 −10 −2 s −1 .…”
Section: Introductionunclassified